A prospective observational study of needle-handling practices at a University Veterinary Teaching Hospital. Issue 2 (3rd March 2016) - Riley, CB; McCallum, S; MacDonald, JA; Hill, KE
Abstract: AIM: To determine the period prevalence of needlestick injury (NSI) at the Massey University Veterinary Teaching Hospital (VTH) and to identify handling and disposal practices that may contribute to the risk of NSI. METHODS: Observations of personnel were conducted in the equine (EVH) and companion animal (CAH) clinics of the VTH during scheduled clinical activities over 9- and 10-day periods, respectively. The number and type of NSI incidents, needle uncapping, capping and disposal events were recorded for veterinarians, nurses and other personnel (visitors and students). The number of needle-related practices, as a proportion of observations, were compared between CAH and EVH, and veterinarians, nurses and others using χ 2 tests. RESULTS: Needlestick injury was not observed during 190 and 163 needle handling and disposal observations in the CAH and EVH, respectively. Uncapping of needles by mouth was observed and was practised more by veterinarians (15/119; 13%) than nurses (2/42; 5%) and others (6/193; 3%) (p=0.001). Two-handed needle recapping after use was observed 265/354 times, and the one handed scooping technique was rarely observed (8/352). In the case of needle disposal, EVH workers used a container that was not purpose built for disposal more than CAH staff (p=0.02), or placed them in a pocket more frequently (p=0.003). Needle disposal containers were available on adjacent bench tops for 65/190 (34%) CAH observations, but no EVH observations. For 51/163 (31%) EVH observations the needle disposal containers were located on the ground, whereas none were observed there in the CAH. No approved sharps containers were observed in the immediate EVH and CAH work areas for 47/163 (28.8%) and 1/191 (0.5%) needle-handling activities, respectively. CONCLUSIONS: Unsafe needle-handling practices must be reduced by policies and training programmes to encourage safe needle-related practices, and ensuring that approved sharps containers are available in close proximity to where needles are used.